Microphysogobio nudiventris, a new species of gudgeon (Teleostei: Cyprinidae) from the middle Chang-Jiang (Yangtze River) basin, Hubei Province, South China - Jiang, Zhong-Guan; Gao, Er-Hu; Zhang, E (Zootaxa, 2012)
Microphysogobio nudiventris, new species, is described from the Du-He, a tributary flowing into the Han-Jiang of themiddle Chang-Jiang (Yangtze River) basin, in Zhushan County, Hubei Province, South China. It belongs in theincompletely scaled group of this genus, but differs from all other species of this group except M. yaluensis, M. rapidus,and M. wulonghensis in the presence of a scaleless midventral region of the body extending more than two-thirds of thedistance from the pectoral-fin insertion to the pelvic-fin insertion. This new species differs from M. yaluensis in theslightly concave or straight distal edge of the dorsal fin, interorbital width, and snout length; from M. rapidus in thenumber of perforated scales on the lateral line and number of pectoral-fin rays, and the placement of the anus; and fromM. wulonghensis in having the two lateral lobes of the lower lip posteromedially disconnected, the shape of the median mental pad of the lower lip, and the number of circumpeduncular scales.